A mobile voice search client for European Portuguese - Pascoal, P. B.; Baldewijns, D.; Pinto, F. M.; Ribeiro, M.; Santos, J.; Dias, M. S. (Interação 2013 - 5ª Conferência Nacional sobre Interação, 2020)
The generalization of speech technology availability notable in simple mobility scenarios, such as searching the Internet using the user´s voice or “voice search”, has increased user awareness of the usefulness of this human-computer interaction modality. In this paper, we present a mobile voice search client that accepts a generic spoken query and presents the search engine’s result page using European Portuguese.